(untitled) (Revista Iberoamericana de Bioética, 2020)
The current pandemic caused by COVID-19 has posed a global challenge that has erupted abruptly in all countries. This pandemic will be overcome, like any other pathology, when a specific treatment is found, but for now that remains non-existent. Until that becomes a reality, the infectious agent is generating a major public health problem that is forcing a limitation of constitutional rights in favour of health protection, and a potential inability of health systems to offer the assistance requires with the best quality standards, especially in the more serious stages of the disease. Bioethics cannot be excluded from this pandemic and must be the best guarantor to offer protection in difficult situations for both healthcare professionals and patients.